O artista da dança: Uma perspectiva de formação na cidade de São Luís - PINTO, Erivelto Viana (2021)
“The dance artist: a perspective of training in the city of São Luís”, is based on my professional artistic career, and intensified in experiences, practices and in the production of contexts and environments for experimentation and study for researchers of dance and the scenic arts in the capital of Maranhão, where I highlight the festival Conecta Dança, a set of actions interested in the diversity of languages, perspectives of creation and research in the contemporary artistic universe for dance and performance, being the basis of this master's research. “The dance artist: a training perspective in the city of São Luís”, is an important topic for the field of performing arts and comes to broaden the discussion on dance training from a historical and reflective exercise on “how it happens the training of dance artists in São Luís”, so I was directed to map individual dance artists working in the city of São Luís between (2017 - 2021). As a result of social distancing, taken by covid 19, I opted for an online questionnaire called Formative Mapping of the Dance Artist in the city of São Luís, where aspects that encompass the artistic-formative dimension of the respondents were raised. It is necessary to look at the history of local dance through interviews, newspapers, blogs and event programs in dialogue with a literature of Brazilian dance researchers. The research also takes a specific look at scenic dance and situates a relevant moment in national dance driven by culture funding policies that create a series of mechanisms through public notices and sponsorships (state and national). “The dance artist: a perspective of training in the city of São Luís”, helps to understand the local performance by identifying possibilities and perspectives in the training of the dance artist in the city, such as the need for formal environments to exist in the coexistence of informal environments, coexisting, where one can discuss the curricula of these spaces and their creation (universities and technical courses), and continuing education. The hybrid formation of this artist. Questions that point to prospects for continuity and unfolding of this work. Keywords: